States of incarceration : rebellion, reform, and America's punishment system - Shanahan, Jarrod; Kurti, Zhandarka (Field notes (London, England), 2022)
"Inspired by the George Floyd Rebellion, States of Incarceration examines the ongoing reconfiguration of mass incarceration as crucial for understanding how race, class and punishment shape America today. The rise of mass incarceration has coincided with a massive disinvestment in working-class communities, particularly communities of colour, and a commitment to criminalize poverty, addiction and interpersonal violence. As Jarrod Shanahan and Zhandarka Kurti argue, the present is a moment of transition and potential reform of incarceration and, by extension, the American justice system. States of Incarceration provides insights into the rise of mass incarceration and its recent history while focusing on the needs of campaigners struggling with the issues of police and prison abolition, as well as the challenges that lie ahead. It is essential reading for anyone concerned with these questions."--